Incidence of Mycotoxins in Local and Branded Samples of Chocolates Marketed in Pakistan - Narjis Naz; Aiza Kashif; Kinza Kanwal; Humayun Ajaz (Journal of Food Quality)
The present overview was intended to evaluate the degree of total aflatoxins and ochratoxin A contamination in different samples of bitter, dark, milk, and white chocolates marketed in Pakistan. For that exploration, two hundred (n=200) samples of chocolates, 100 branded and 100 local, were analyzed for mycotoxins profile by HPLC-FLD. The outcomes firmly sustained that the majority of the samples were contaminated with aflatoxins and ochratoxin A. The incidence of total aflatoxins and ochratoxin A in branded samples was 83% and 90%, whereas the local samples showed 91% and 97% contamination, respectively. The highest amount of total aflatoxins was found in branded dark chocolates, that is, 2.27 μg/kg, and maximum ochratoxin A level was detected white chocolates (2.06 μg/kg). On average, the local white chocolates and dark chocolates faced the highest level of total aflatoxins (3.35 μg/kg) and ochratoxin A (3.48 μg/kg), respectively. The local samples of chocolates were more contaminated with mycotoxins as compared to branded ones accredited to the lack of quality control and quality assurance during the manufacturing as well as packing processes. In recent years, consumption of chocolate is rapidly increasing especially by young generation, so monitoring of mycotoxin occurrence in them is a matter of great concern and more studies are required to comprehend the production of mycotoxins in these products.